Effect of wind on summer chlorophyll-a variability in the Yellow Sea - Lin, Lei; Liu, Dongyan; Wang, Yueqi; Lv, Ting; Zhao, Yue; Tan, Wei (Frontiers in Marine Science, 2023)
Winds potentially affect primary production in shelf seas during the stratified season by enhancing upwelling and mixing. However, the exact extent and modalities of this effect in the Yellow Sea remain unclear. Here, based on the satellite and in situ observation data, statistical method, and wind-driven upwelling theory, we examined the wind effect on the chlorophyll-a (Chl-a) variability in the summer of 2002-2020 and the effect mechanism. The satellite data revealed a significantly positive correlation between anomalies of the monthly mean of the summer sea surface Chl-a and wind speed at the continental slope region (water depth of 20-60 m) in the southwestern Yellow Sea where strong wind-driven upwelling has been indicated by previous studies. The wind-driven upwelling along the continental slope was further verified using two summer in-situ observations. After a fortnight of southeasterly wind, the upwelling patterns of high salinity and rich nutrients from the Yellow Sea cold water mass were observed, and consequently, high Chl-a concentrations occurred in the upper layer of the slope region. The wind-driven upwelling occurred in the region at water depth of 20-60 m, which is consistent with the result of the wind-driven coastal upwelling theory (0.5D < water depth < 1.25D, where D is the thickness of the Ekman layer). The dissolved inorganic nitrogen, phosphorus, and silicate fluxes contributed by wind-driven upwelling were estimated as 1345 ± 674 μmol/m2/d, 81 ± 45 μmol/m2/d and 1460 ± 899 μmol/m2/d, respectively, accounting for 30%-40% of total nutrient supply, and were several times larger than that contributed by the turbulent mixing, which can explain why the strong wind-Chl-a correlation only occurred at the upwelling region rather than the entire sea. In addition, in this region, the interannual variability of the summer mean Chl-a was negatively correlated to both the Pacific Decadal Oscillation (PDO) and El Niño-Southern Oscillation (ENSO) indexes, due to the opposite phase of the summer wind anomaly and the PDO/ENSO. This study revealed the wind effect on the shelf phytoplankton is regional and highlighted that wind could be a pivotal factor driving the climate variability of shelf primary production in the stratified season.